Trichoderma Biofertilizer Links to Altered Soil Chemistry, Altered Microbial Communities, and Improved Grassland Biomass - Zhang, Fengge; Huo, Yunqian; Cobb, Adam B.; Luo, Gongwen; Zhou, Jiqiong; Yang, Gaowen; Wilson, Gail W. T.; Zhang, Yingjun (Frontiers in Microbiology, 2018)
In grasslands, forage and livestock production results in soil nutrients deficit as grasslands typically receive no nutrient inputs, leading to a loss of grassland biomass. The application of mature compost has been shown to effectively increase grassland nutrient availability. However, research on fertilization regime influence and potential microbial ecological regulation mechanisms are rarely conducted in grassland soil. We conducted a two-year experiment in meadow steppe grasslands, focusing on above- and belowground consequences of organic or Trichoderma biofertilizer applications and potential soil microbial ecological mechanisms underlying soil chemistry and microbial community responses. Grassland biomass significantly (p = 0.019) increased following amendment with 9000 kg ha-1 of Trichoderma biofertilizer (composted cattle manure + inoculum) compared with other assessed organic or biofertilizer rates, except for BOF3000 (fertilized with 3000 kg ha-1 biofertilizer). This rate of Trichoderma biofertilizer treatment increased soil antifungal compounds that may suppress pathogenic fungi, potentially partially responsible for improved grassland biomass. Nonmetric multidimensional scaling (NMDS) revealed soil chemistry and fungal communities were all separated by different fertilization regime. Trichoderma biofertilizer (9000 kg ha-1) increased relative abundances of Archaeorhizomyces and Trichoderma while decreasing Ophiosphaerella. Trichoderma can improve grassland biomass, while Ophiosphaerella has the opposite effect as it may secrete metabolites causing grass necrosis. Correlations between soil properties and microbial genera showed plant-available phosphorus may influence grassland biomass by increasing Archaeorhizomyces and Trichoderma while reducing Ophiosphaerella. According to our structural equation modeling (SEM), Trichoderma abundance was the primary contributor to aboveground grassland biomass. Our results suggest Trichoderma biofertilizer could be an important tool for management of soils and ultimately grassland plant biomass.